The Difference between Student’s Ability in Writing Story through Guided Pictures and Guided Words at The Second Semester of Laboratory Students University of Muhammadiyah Jakarta - Rosidah, Siti Latifatul; Sitepu , Setiana Sri Wahyuni; Maisari , Linda (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Having good skill in writing is also needed in a teaching learning process. There are some methods that influence the success of English language teaching. One of these is writing through pictures and words. In this research, the researchers want to use them to compare the students’ ability in writing stories through guided pictures and guided words. This research is to know the students’ ability in writing story through guided pictures and guided words, and whether there is any significant difference between them. The design of this study is descriptive quantitative that studies on the comparison between writing story through guided pictures and guided words. The population of this study is the second semester students of English Laboratory at Faculty of Economics and Business University of Muhammadiyah Jakarta that consists of 3 classes. Then, the samples of this study are the students at Lab A13 that consists of 24 students. The technique sampling of this study is purposive sampling. Then, the instrument of this study is a writing test. The test is done by giving a list of words and a set of pictures to the students. The data of this test is analyzed using the t-test method. The result of this study is that there is no significant difference between students’ ability in writing stories through guided pictures and guided words. Writing through guided pictures has an average score of 69.6 and writing through guided words has an average score of 65.7. Then, the result of data analysis gets the score 1,95 and the significant 5% of table “t” is 2,015. Therefore, -2,015˂1,95˂2,015 means that the null hypothesis is accepted and the alternative hypothesis is rejected.